Planting date effects on sweet sorghum in São Manuel and Botucatu, São Paulo state, Brazil - Machado, José Ricardo; Nakagawa, João; Rosolem, Ciro A.; Brinholi, O. (Pesquisa Agropecuaria Brasileira, 2014)
The purpose of the present research was to study the behavior of sweet sorghum (Sorghum bicolor (L) Moench) cv. Brandes planted in different dates. Two experiments were carried out under field conditions on Oxisols, a Dark Red Latosol sandy phase in São Manuel and a Duski Latossol (clay) in Botucatu, São Paulo State, Brazil. Sweet sorghum was planted from September to February, at 20 days intervals. The results allowed for the conclusion that the duration of development stages of sweet sorghum plants decreased from the first to the last planting date. November was the best month to plant sweet sorghum for stalk production in both locations. Although planting could be made since late September to early December, decreases in the stalk yield are expected when it is made out of the best month. The highest stalk yield was obtained from plants that presented high number of internodes, high height and diameter of stalk, resulting in plants with development and vigour.